Millimetre-Wave Propagation Channel Based on NYUSIM Channel Model With Consideration of Rain Fade in Tropical Climates - Asma Ali Budalal; Ibraheem Shayea; Md. Rafiqul Islam; Marwan Hadri Azmi; Sawsan Ali Saad; Yousef Ibrahim Daradkeh; Hafizal Mohamad (IEEE, 2024)
Indexed by Scopus/ERA